Cat among the pigeons - Christie, Agatha (HarperCollinsPublishers London, 2002)
The unpopular games mistress is found, shot through the heart from point blank range. The school is thrown into chaos when the "cat" strikes again. Unfortunately, schoolgirl Julia Upjohn knows too much. In particular, she knows that without Hercule Poirot's help, she will be the next victim